CHALLENGES AND PROSPECTS FOR EXPANDING ACCESS TO PROMISING FOREIGN LABOR MARKETS FOR CITIZENS OF UZBEKISTAN - Farkhod Abdurakhmonov,; Sunnatilla Tursunov, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This study employed a mixed-methods approach to comprehensively examine the supply and demand dynamics of foreign labor markets for citizens of Uzbekistan. The primary objectives included an in-depth analysis of current migration and emigration trends, the assessment of bilateral labor agreements with governments of countries offering high employment potential for Uzbek nationals, and the evaluation of the scope and effectiveness of vocational training programs designed to prepare individuals with secondary education for employment abroad.